Analisis kepuasan nasabah bank terhadap pelayanan mobile banking di masa pandemi Covid-19 - Puspasari, Nelly; Said, Laila Refiana; Rusniati, Rusniati (Jurnal Manajemen, 2022)
This study aimed to analyze the variables of E-Service Quality, Customer Satisfaction, and Positive Word-of-Mouth use of Bank Kalsel mobile during the Covid 19 pandemic. The data analysis method for 97 customers in this study was Partial Least Square- Structural Equation Modeling (PLS-SEM). The results showed that (1) E-Service Quality did not affect Positive Word-of-Mouth; (2) E-Service Quality affected Customer Satisfaction; (3) Customer Satisfaction affected Positive Word-of-Mouth; (4) E-Service Quality affected Positive Word-of-Mouth through Customer Satisfaction as an intervening variable. This study proved that the mediation variable Customer Satisfaction played a very important role and bridging the influence of the quality of mobile banking services with the intention of customers to conduct positive word-of-mouth communication about the bank’s services. The implication is that no matter how good the quality of mobile banking services is perceived by bank management when customers do not feel satisfied, the positive word-of-mouth desired by banks from their customers will never be realized. Bank Kalsel management needs to periodically pay attention to and evaluate the quality of E-Service Quality, especially in terms of Efficiency, System availability, Fulfillment and Privacy. These factors have the value that affects Customer Satisfaction and Positive Word-of-Mouth.